Answer: y = 1
Explanation:
Step 1) Simplifying
2(y + 2) = 6
Step 2) Reorder the terms:
2(2 + y) = 6
(2 * 2 + y * 2) = 6
(4 + 2y) = 6
Step 3) Solving
4 + 2y = 6
Step 4) Solving for variable 'y'.
Step 5) Move all terms containing y to the left, all other terms to the right.
Step 6) Add '-4' to each side of the equation.
4 + -4 + 2y = 6 + -4
Step 7) Combine like terms: 4 + -4 = 0
0 + 2y = 6 + -4
2y = 6 + -4
Step 8) Combine like terms: 6 + -4 = 2
2y = 2
Step 9) Divide each side by '2'.
y = 1
Step 10) implifying
y = 1